Race, social media news use, and political participation. Issue 1 (2nd January 2022) - Wang, Luxuan
ABSTRACT: This research examines how race moderates the association between social media news consumption and political participation. Through an analysis of Pew Research Center survey data, this study finds that social networking sites (SNS) are crucial for racial minorities' political participation. Racial minorities showed a higher level of SNS usage for news consumption, and Black people exhibited significantly higher levels of online political participation than White people, especially when SNS news consumption was at a low frequency. Yet the association between SNS news use and online participation was stronger for White people than Black people. In contrast, this research did not find a significant racial gap in offline voting engagement nor extra democratic benefits of SNS news consumption for racial minorities.